Changes in the granulometric composition of a product overgranulated by balling with the use of "fattening" technology - Yu. A. Taran; R. V. Morozov; A. V. Taran; A. L. Taran (Тонкие химические технологии)
In the paper we present the method of calculating the particle size distribution of the initial granules overgranulated by the “fattening” technology. We have developed a number of different ways for solving the problem for the continuous and periodic (transition) process. Knowing the particle size distribution is very important for calculating and planning the production of granulated products, such as fertilizers and many others. Fattening is a process of overgranulating the initial pellet by the powder (with or without binding) by rolling in different devices, including plate granulators. The calculation results obtained with the use of the models are represented as a series of graphic dependencies. A comparison of the proposed calculation methods with those previously known is also given. A block diagram of the implementation of the algorithm is also presented in the paper.